Effectiveness and Efficiency of Physical and Chemical Mutagens in Fennel - Mahla, H R; Ramkrishna, K (Annals of Arid Zone, 2016)
In the present study, mutagenic effectiveness and efficiency of gamma rays. sodium azide, ethyl methane sulphonate (EMS) and their combinations were estimated in fennel cv. RF-I 0 I. A steady reduction in germination. subsequent survival and pollen fertility was observed with the increasing doses of the mutagens. The efficiency of mutagenic treatment increased with the dose of the mutagen. Azide at 3 mM had maximum efficiency (0.976). followed by EMS at 0.50% (0.760). Magnitude of effectiveness als.o increased with increase in the dose of the mutagen. Sodium azide was found to be the most effective, being 24-fold as effective as EMS and 3 10 times as gamma rays.